2001
DOI: 10.1046/j.1365-2141.2001.03187.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of protein C receptor expression in monocytes

Abstract: Summary. Many sequelae associated with endotoxaemicinduced shock result from excessive production of the cytokine mediators, tumour necrosis factor alpha (TNF-a), interleukin 1 (IL-1) and IL-6 from lipopolysaccharide (LPS)-activated monocytes. Protein C (PC)/activated protein C (APC) has potent cytokine-modifying properties and is protective in animal models and human clinical trials of sepsis. The precise mechanism by which this antiinflammatory response is achieved remains unknown; however, the recently desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 39 publications
2
64
1
Order By: Relevance
“…EPCR is a 46-kd type I transmembrane glycoprotein that is homologous to class I major histocompatibility complex/CD1 family of proteins (19,23). It is predominantly expressed by endothelial cells, mainly those of larger blood vessels, although recent reports have shown it to be present on some leukocytes of the innate immune system (21,42), including RA monocytes (Xue M, et al: unpublished observations). Using a blocking antibody, we have shown that EPCR is required for APC inhibition of MMP-9 in monocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPCR is a 46-kd type I transmembrane glycoprotein that is homologous to class I major histocompatibility complex/CD1 family of proteins (19,23). It is predominantly expressed by endothelial cells, mainly those of larger blood vessels, although recent reports have shown it to be present on some leukocytes of the innate immune system (21,42), including RA monocytes (Xue M, et al: unpublished observations). Using a blocking antibody, we have shown that EPCR is required for APC inhibition of MMP-9 in monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The conversion to APC is augmented in the presence of the specific receptor endothelial protein C receptor (EPCR) (19), which is expressed on the surface of endothelial cells, keratinocytes (20), and some leukocytes, including neutrophils and monocytes (21). In addition, APC is now recognized as playing a key role in the regulation of inflammation by down-regulating leukocyte activation and inflammatory cytokine production (22).…”
mentioning
confidence: 99%
“…It is possible that a unique lipid or a composition of lipids not related to the lipid rafts could be responsible for a high monocyte TF activity when this protein is presented in a native environment. Alternatively, a TF receptor similar to those for protein C (Galligan et al , 2001 ), factors X and Xa (McGee and Rothberger , 1986 ;Altieri et al , 1988 ;Worfolk et al , 1995 ), and the prothrombinase complex (Tracy et al , 1985 ) could be the cause of this phenomenon. Further studies are required to elucidate the nature of high monocyte TF activity.…”
Section: Tf Environment and Activitymentioning
confidence: 99%
“…To date, the only known cellular receptor for activated protein C is the EPCR, a 46-kDa singlechain transmembrane glycoprotein homologous to the MHC class I/CD1 family of molecules (33). EPCR was identified originally on vascular endothelial cells and has since been detected in neutrophils (34), monocytes (34), and in the monocytic cell line THP-1 (35). Recent studies in endothelial cells suggest that the antiapoptotic effect of activated protein C is mediated by EPCR and PAR-1 and EPCR (19 -21).…”
Section: Requirement Of Epcr and Par-1 For The Antiapoptotic Effect Omentioning
confidence: 99%